National Sheep and Goat Breeding Program and Breeder Associations’ collaboration systems of Turkey - Daskiran I.; Ayhan V. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
major goat breeding countries in Europe and it has approximately 7.2 million goat population with attractive breeding systems and genetic diversity. Some major Turkish goat breeds are Angora, Kilis, Damascus, Hair goat and Honamli goat. The goat population in Turkey is mainly composed of the Hair goat (97%) (Anatolian Black), and the rest of goats belong to different local types. The Hair goat serves multiple purposes (mainly meat and milk), but it’s productivity is quite low. Goat production is distributed to whole of Turkey, especially at mountainous areas of Mediterranean, South-East Anatolia and South-West Anatolia regions and production systems are basically extensive and semi-extensive. On the other hand last ten years private sector investment has been increasing especially in the west part of Turkey. Due to the decrease in the number of goats in Turkey during the last ten years, the Ministry of Food, Agri culture and Livestock (MFAL) has started National Sheep and Goat Breeding Program with breeders and their organizations (Turkish Sheep and Goat Breeders Association). Project started working with 2 breeds (Akkaraman Sheep and Angora Goat) and it has reached to 12 sheep&goat breeds, 472 breeders and 80,000 animals in the first stage. In the second stage, the project was expanded, due to its efficiency and to the requests of breeders. It is continuing with 29 national sheep and goat breeds and approximately 800,000 animals. This project has multiple partners (Breeders associations, Universities, Research Institutes of MFAL) and it aims to improve native pure-bred species together with sheep and goat yields and at the same time set up a national breeding program for goat and sheep production.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)